Vulnerability for alcohol use disorder after adverse childhood experiences (AUDACE): protocol for a longitudinal fMRI study assessing neuropsychobiological risk factors for relapse. Issue 6 (30th June 2022) - Türkmen, Cagdas; Machunze, Noah; Tan, Haoye; Gerhardt, Sarah; Kiefer, Falk; Vollstädt-Klein, Sabine
Abstract : Background: Adverse childhood experiences (ACE) are common and may predispose affected individuals to various health problems, including alcohol use disorder (AUD). Although a relationship between ACE and AUD has been well-established, potential mechanisms that may underlie this relationship remain to be elucidated. The importance of these mechanisms with respect to relapse risk is of particular interest, given the clinical relevance of relapse in addictions. Thus, the aim of this study is to longitudinally assess the role of clinically relevant variables in the relationship between ACE and AUD, namely stress sensitivity, emotion processing, cue reactivity and cognitive functioning (response inhibition and working memory), in relation to relapse risk. Methods and analysis: In this observational, longitudinal case-control study, 36 patients with AUD and heavy drinkers with varying degrees of ACE from a previous project (NCT03758053 ) as well as newly recruited participants from the same study population will be assessed. Besides measuring long-term relapse in AUD by re-examining these 36 previous participants after 2–2.5 years, factors contributing to short-term relapse will be examined by reassessing all participants on a 3-month follow-up. Furthermore, participants with no or mild ACE will be compared with participants with moderate to severe ACE to assess between-subject differences in risk factors for AUD. Questionnaires and interviews will thus be used to cover individuals' drinking behaviour and ACE. Emotion processing, stress sensitivity, cue reactivity and cognitive functioning will be assessed using task-based functional MRI (fMRI). Additionally, saliva cortisol and blood samples will be taken to measure hormonal stress response and to perform genome wide association analyses, respectively. The general linear model will be applied on the first level fMRI analyses, whereas for the second level analyses and analyses of behavioural data, t-tests, regression analyses, repeated-measures and one-way analysis of variances will be used. Ethics and dissemination: This study has been approved by the ethics committee of the Medical Faculty Mannheim of Heidelberg University (ethics approval number: 2018-560N-MA with amendment from 29 June 2021). The findings of this study will be presented at conferences and published in peer-reviewed journals. Trial registration number: NCT05048758 ; Pre-results, clinicaltrials.gov.